ANALISIS STRATEGI PEMBERDAYAAN PETANI LADANG DI KABUPATEN KONAWE KEPULAUAN (The Empowerment Strategies For Swidden Agriculture Farmers In Konawe Islands District) - SITTI ROSMALAH; HARIANTI HARIANTI; NURMAYA NURMAYA (Universitas Mulawarman (University of Mulawarman), 2023)
This research aims to formulate farmer empowerment strategies on field rice farming in Konawe Islands Regency. This research is classified as descriptive research that combines qualitative and quantitative approaches. The data analysis used to formulate the strategy is SWOT analysis. This analysis identifies internal factors owned by farmers in the form of strengths and weaknesses and external factors owned by field farmers in the form of opportunities and threats. Informants in this study came from the village head, counsellor, field farmers and community leaders. The research findings show that effective empowerment strategies applied to field farmers in Konawe Islands Regency are: a. Combining field farming patterns with plantation patterns to obtain additional income b. Increasing the capacity and support of the government and related agencies such as the agriculture service/extension agency to farmer groups through coaching and participation in development programs c. Building togetherness of farmer groups to continue to trust each other, share fate and mutual cooperation so that it becomes a strength in strengthening the group d. Making farmer economic institutions such as BUMDes effective to help farmers' economic problems e. Increase farmers' knowledge about the benefits of groups through counseling, training and mentoring.